Non-prescription antibiotic use for cough among Chinese children under 5 years of age: a community-based cross-sectional study - Rui Yan; Yao Zhu; Shuying Luo; Xuan Deng; Xuewen Tang; Zhujun Shao; Hanqing He (BMJ Open)
Objective This study aimed to investigate the non-prescription use of antibiotics for cough among children under 5 years in China.Design A community-based cross-sectional survey.Setting A face-to-face interview based on a standard questionnaire in the community from October to December 2019.Participants A total of 3102 children under 5 years of age were enrolled with probability proportionate to size sampling method. The children’s caregivers provided the responses as their agents.Outcome measures Cough in the past month, non-prescription use of antibiotics after cough.Results 1211 of 3102 children were reported to have a cough in the past month. Of these, 40.2% (487/1211) were medicated with antibiotics, and 18.7% (91/487) of these were not prescribed. Cephalosporins were the most frequently used antibiotic (52.8%), and community pharmacies were the main source (53.7%). Children who coughed for 1–2 weeks (OR 1.73, 95% CI 1.03 to 2.90) or 3–4 weeks (OR 2.39, 95% CI 1.08 to 4.97), with runny nose (OR 1.86, 95% CI 1.13 to 3.19) or those whose family annual income between ¥50 000 and ¥100 000 (OR 4.44, 95% CI 1.52 to 18.95) had a higher risk of non-prescription use of antibiotics than those coughing for <1 week, without runny nose or with family annual income <¥50 000.Conclusions Our findings indicated that a high proportion of infants and young children had been treated with antibiotics for cough, and nearly one in five of them were used without prescription. More public health campaigns and further education on the appropriate use of antibiotics are needed to ensure the rational treatment of cough in children.